O68 Emrocs – emergency medicine regionally organised collaborative simulation: standardising sepsis care. (5th November 2017) - Watters, C; Weatherup, N; McKenna, C; Greenwood, E; McKee, L; McCullough, S; Baylis, P; ONeill, G; Mitchelson, M; Bannon, O; Magowan, E; McCullough, L; et al.
Abstract : Background: In order to deliver quality sepsis care to all patients throughout the region of Northern Ireland a group of Emergency Medicine simulation enthusiasts got together to improve the quality of care across all ten type 1 emergency departments. Project Description: A review of the evidence in sepsis care was carried out and each department ensured adherence. A representative from each department presented its current sepsis care pathway and as such best practice was shared throughout the region. Methodology: An in-situ simulation scenario was designed to introduce best practice to each department. Pre and post intervention data was collected and all personnel involved in the in-situ simulations completed a questionnaire. Outcomes: Outcomes include an improvement in sepsis detection rates within emergency departments and also improvements in completion of the sepsis 6 bundle. There was also a reported increase in the number of personnel able to diagnose sepsis and improved knowledge of its treatment bundle. Other outcomes include the introduction of a standardised approach to sepsis management and documentation throughout the region. All type 1 emergency departments now utilise either Sepsis boxes or trolleys which include equipment and medications required to complete the sepsis 6 bundle in a timely fashion. Recording of sepsis diagnostic criteria and sepsis 6 interventions including timings has also been standardised through the introduction of proformas/stickers. Unexpected, but we believe equally as important outcomes include, the introduction of in-situ simulation across all type 1 emergency departments, introduction/improvements in collaborative working and Interprofessional education sessions, a greater understanding around latent threat detection and the benefits of simulation to drive quality improvement and to test systems and processes within clinical settings. Conclusions: We have utilised in-situ simulation as a vehicle to explore and disseminate sepsis best practice, to improve the quality of sepsis care on a regional level, while reducing variation and standardising care. Through this project we have also showcased the many benefits that simulation has to offer, and as such have inspired many more healthcare personnel from managerial/executive teams to medical, nursing and allied health professionals to improve the quality of the care we deliver to our patients. To build on this success we intend to apply this model to other areas through in-situ simulation, such as trauma, asthma, neck of femur fractures and procedural sedation. Through these efforts we believe we can improve the quality of care we deliver to our patients.